2012
DOI: 10.1073/pnas.1118467109
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of cytochrome P4501-dependent clearance of the endogenous agonist FICZ as a mechanism for activation of the aryl hydrocarbon receptor

Abstract: Altered systemic levels of 6-formylindolo [3,2-b]carbazole (FICZ), an enigmatic endogenous ligand for the aryl hydrocarbon receptor (AHR), may explain adverse physiological responses evoked by small natural and anthropogenic molecules as well as by oxidative stress and light. We demonstrate here that several different chemical compounds can inhibit the metabolism of FICZ, thereby disrupting the autoregulatory feedback control of cytochrome P4501 systems and other proteins whose expression is regulated by AHR. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
222
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 185 publications
(238 citation statements)
references
References 52 publications
13
222
3
Order By: Relevance
“…The increase in CYP1A1 activity leads to H 2 O 2 production. An increase in cellular levels of H 2 O 2 has been linked to several key alternations in cells leading to cancer including DNA alternation, cell proliferation, apoptosis resistance, metastasis, angiogenesis and hypoxia-inducible factor 1 (Androutsopoulos et al, 2009;Wincent et al, 2012). In current study statistically significant downregulation of GSTP1 was observed in brain tumor samples compared to control samples.…”
Section: Discussionsupporting
confidence: 48%
“…The increase in CYP1A1 activity leads to H 2 O 2 production. An increase in cellular levels of H 2 O 2 has been linked to several key alternations in cells leading to cancer including DNA alternation, cell proliferation, apoptosis resistance, metastasis, angiogenesis and hypoxia-inducible factor 1 (Androutsopoulos et al, 2009;Wincent et al, 2012). In current study statistically significant downregulation of GSTP1 was observed in brain tumor samples compared to control samples.…”
Section: Discussionsupporting
confidence: 48%
“…42 Although a comparison between receptor activation and loss-of-function experiments has to be interpreted carefully, the observed repressive action of AHR on gene expression in the absence of any exogenous ligands may point to the potential presence of endogenous AHR ligands. 12 Noteworthy, a nuclear-localized constitutively active AHR that blocks gene expression, probably by inducing local epigenetic modifications, has also been previously described. 43,44 Whether the AHR directly binds the p27 KIP1 promoter to repress transcription is not known up-to-now.…”
Section: Discussionmentioning
confidence: 99%
“…11 More precisely, UVB rays are absorbed by free tryptophan in the cytosol of KC, resulting in the formation of the tryptophan-photoproduct 6-formylindolo [3,2-b]carbazole (FICZ), 10 a high-affinity ligand of the AHR. 12 Alike polycyclic aromatic hydrocarbons (PAHs) and dioxins, FICZ binds to the AHR and initiates the dissociation of the cytosolic AHR multiprotein complex, consisting of heat-shock protein 90, tyrosine kinase c-src, and other co-chaperones, thereby enabling the nuclear translocation of AHR. 10,11 In the nucleus, the AHR dimerizes with ARNT (AHR nuclear translocator) and binds to xenobiotic-responsive elements (XRE) in the promoter region of genes to enforce their transcription.…”
mentioning
confidence: 99%
“…In a note of caution, such assays may not always reflect AhR ligand binding in the LBD. In particular, oxidative stress, inflammatory mediators, and many physical stress factors (exposures that strongly suppress CYP1A1 transcription if added together with inducers such as TCDD or Aryl Hydrocarbon Receptor in Immunology and Toxicology b-naphthoflavone) have repeatedly been demonstrated to activate AhR-dependent transcription by themselves without direct binding (Gonder et al, 1985;Crawford et al, 1997;Tanaka et al, 2005;Becker et al, 2006;McMillan and Bradfield, 2007;Afaq et al, 2009;AnwarMohamed et al, 2009;Wincent et al, 2012). Electrophoretic band shifts exhibiting formation of AhR-AhRE complexes have been detected with nuclear extracts from cells cultured in the absence of added ligands and in cells subjected to various stressful conditions (e.g., hyperoxia, metals, low temperature, immune cell activators, the proteolysis inhibitor MG132 (carbobenzoxy-L-leucyl-Lleucyl-L-leucinal), or detached growth (Sadek and AllenHoffmann, 1994;Crawford et al, 1997;Monk et al, 2001;Santiago-Josefat et al, 2001;Tamaki et al, 2005;Elbekai and El-Kadi, 2007).…”
Section: The Realm Of Aryl Hydrocarbon Receptor Ligands: Agonistsmentioning
confidence: 99%
“…There appears to be only one ligand binding pocket in the AhR [in the Per-ARNT-Sim-B domain], and the binding affinity of the best characterized highaffinity ligand, TCDD (2,3,7,8-tetrachlorodibenzo-pdioxin), depends on only a few amino acids in the binding pocket of the AhR, as demonstrated by modeling and mutation studies (Whelan et al, 2010;DeGroot et al, 2012;Wu et al, 2013). The AhR can also be activated by numerous stress factors and substances that may not fit into the binding pocket, such as hyperoxia, oxidized low-density lipoproteins, hydrogen peroxide, ozone, or metals (references in Wincent et al, 2012). Much of this is not understood because the AhR has not yet been crystallized, although it was cloned more than 2 decades ago (Burbach et al, 1992).…”
Section: Introductionmentioning
confidence: 99%